2012
DOI: 10.5897/ajb11.3271
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy-breaking and salinity/water stress effects on seed germination of Atlas cypress, an endemic and threatened coniferous species in Morocco

Abstract: Atlas cypress (Cupressus atlantica Gaussen) is an endemic coniferous medicinal species geographically restricted to the N'Fis valley river in the High Atlas Mountains in SouthWestern Morocco. Eight dormancy-breaking treatments, 5 NaCl concentrations, and 5 water potentials were tested on the germination of Altas cypress seeds that had been stored in a cold room for 5 years after collecting from Aghbar population. Hand scarification, gibberellic acid and hot water increased the seed germination percentage (up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…After 30 days of assessment, it was observed that germination performance was highest for seeds extracted from cones that had been soaked in cold water. Several studies have been conducted on the effects of soaking media on seed germination, with the present study focusing on soaking cypress cones in cold and hot water and their influences on germination [37][38][39][40].…”
Section: Cupressus Lusitanicamentioning
confidence: 99%
“…After 30 days of assessment, it was observed that germination performance was highest for seeds extracted from cones that had been soaked in cold water. Several studies have been conducted on the effects of soaking media on seed germination, with the present study focusing on soaking cypress cones in cold and hot water and their influences on germination [37][38][39][40].…”
Section: Cupressus Lusitanicamentioning
confidence: 99%